Trace element composition and U-Pb ages of cassiterite from the Bolivian tin belt - Gemmrich, Laura (2021)
The Bolivian tin belt is a metallogenic province in the Eastern Cordillera of the Andes known for its Sn, W, Ag, and base metal deposits. Cassiterite, which is a major constituent in many magmatic-hydrothermal ore deposits from the Bolivian tin belt, can incorporate dozens of elements within its crystal lattice, making it a useful geological tracer mineral and also a potential host of critical elements. New U-Pb dating of cassiterite yields Late Triassic (Kellhuani deposit) and Late Oligocene to earliest Miocene (Viloco, Huanuni, and Llallagua deposits) ages. These ages confirm that Sn mineralization in the Bolivian tin belt occurred at least in two separate events during two major magmatic episodes apparently triggered by mantle upwelling, decompression melting, and basalt production promoting high heat flow into the overlying crust. The composition of studied hydrothermal cassiterite yields some geochemical trends that are attributed to its distance to the causative intrusion and/or level of emplacement. For example, cassiterite is generally enriched in Nb and Ta and yields higher Ti/Zr and Ti/Sc ratios in samples from xenothermal ore deposits located adjacent to intrusive complexes relative to shallow xenothermal and epithermal ore deposits. Therefore, these geochemical trends in cassiterite are useful tracers pointing to magmatic-hydrothermal centers. REE distribution in cassiterite was likely influenced by boiling processes, which resulted in tetrad-type irregularities. Cassiterite from the Bolivian tin belt is unattractive as a source for Nb (interquartile range [IQR] 4.84-0.037 ppm), Ta (IQR 0.0924-0.0126 ppm), and Ge (IQR 3.92-0.776 ppm). Some deposits, however, contain cassiterite relatively enriched in In (IQR 96.9-9.78 ppm, up to 1414 ppm) and Ga (IQR 92.1-3.03, up to 7437 ppm), that could constitute an attractive supplementary source for these elements in addition to sulfide minerals in the same deposits.